Corrosion Protection of AA7075 Aluminium Alloy by Trimethoxy-Silanes Self-Assembled Monolayers. (2nd April 2013) - Neves, Rodrigo S.; Silva, Daiane P. B.; Motheo, Artur J.
Abstract : This study presents electrochemical data concerning the aluminium alloy AA7075 surface modified by self-assembled monolayers (SAMs) of octadecyl-trimethoxy-silane and propyl-trimethoxy-silane. Polarisation curves have shown SAMs blocking effect, as they partially block the oxygen reduction reaction and displace the corrosion potential to positive values. Electrochemical impedance spectroscopy experiments have suggested that the protective effect comes from the oxide layer stabilization by the organic monolayers, which block the corroding species diffusion to the surface. These results show the potential of using methoxy-silanes SAMs as corrosion protective coatings; however, they are also indicative of the superior octadecyl-trimethoxy-silane protective characteristics.